Compost and biochar as effective amendments for enhancing the quality of organic soilless growing media - Ha, Nguyen Ngan; Oanh, Le Thi Hoang (Vietnam Journal of Science and Technology, 2026)
Biochar and compost have been recognized as amendments for improving soil quality and crop productivity. However, using biochar and compost, individually or in combination, for creating organic growing media remains less prevalent than in soil applications. This study addresses this gap by combining compost and biochar with coconut coir dust to develop organic soilless growing media. In this study, there were 4 empirical formulas (1 control formula with organic soil and three mixed ones with different proportions of coconut coir dust (40 – 60 %), compost (20 – 40 %), and 20 % of biochar). The physicochemical parameters of feedstocks were evaluated before creating growing media. Organic growing media were assessed as rich in organic matter (40.222 – 50.982 %), while porosity, moisture content, and dry bulk density were in the range of 74.2 – 82.0 %, 55.7 – 58.0 %, and 0.56 – 0.78 g/cm3. pH and EC of growing media were in the range of 6.20 – 6.43 and 1.33 – 1.56 mS/cm. The characteristic parameters of the organic growing media were better than those of the control formula. Green onions cultivated in organic growing media exhibited yields of 1.67 to 2.16 times higher than those grown in the control medium, with no contamination from heavy metals, nitrates, or pathogenic microorganisms. The most effective organic growing medium, comprising 50 % coconut coir dust, 30 % compost, and 20 % biochar, produced the highest yield and quality. These findings demonstrate the potential of organic soilless growing media as a viable alternative to traditional soil in urban agriculture.